THE EFFECT OF TEAMWORK, JOB SATISFACTION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PANDRAH BIREUEN COMMUNITY HEALTH CENTER - Fathi Rizkina; Likdanawati; Yanita; Nurmala (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to examine the extent of the direct influence of Teamwork, Job Satisfaction, and Work Discipline on Employee Performance at the Pandrah Bireuen Community Health Center. The purpose of this study was to determine the level of employee performance in the Pandrah Bireuen Community Health Center. The data used in this study are primary data obtained by distributing questionnaires to 115 employees. The data analysis technique used is multiple linear regression analysis consisting of data instrument testing, classical assumption testing, and hypothesis testing using SPSS software. The results of the study indicate that partially teamwork has a positive and significant effect on employee performance at the Pandrah Bireuen Community Health Center, then Job Satisfaction has a positive and significant effect on employee performance at the Pandrah Bireuen Community Health Center and Work Discipline has a positive and significant effect on employee performance at the Pandrah Bireuen Community Health Center. These findings provide useful implications for the government in establishing strategies related to human resources to improve employee performance.